Exploring practices and effectiveness of bedside teaching in residency training: protocol for a scoping review - Hussain, Sajid; Mat Nor, Mohd Zarawi; Roslan, Nurhanis Syazni; Yusoff, Muhamad Saiful Bahri (Penerbit Universiti Sains Malaysia, 2025)
Bedside teaching (BST) is an indispensable practice in clinical education. To stay ahead of the curve in the rapidly evolving field of clinical education, embracing innovative and effective learning approaches like BST is essential. The first step is to understand the current approaches and practices of BST in the clinical training of the residents by utilising the highly effective Joanna Briggs Institute scoping review guidelines, which will systematically map the approaches and practices in BST over the last 10 years. Primary data will be searched from relevant studies, review articles, and grey literature from January 2013 to July 2023; a three-step search strategy will be employed, consisting of review search, study selection, and evidence charting by involving electronic databases (PubMed, Scopus, EBSCOhost, Google Scholar) and two independent reviewers. A third reviewer is provided in case of disagreements between the two reviewers. After conducting a thorough screening of the eligible studies and importing them into our electronic source, the charting and presentation of the results of the included studies will be done. As a secondary search, ethical approval is not required. This review will probe into the demographic aspects, study designs, various approaches and practices utilised, and their learning attainments in outcomes and better patient care and safety. Traditional and innovative methods are appraised, examining their respective impact on the clinical outcomes, with all efforts to restore this declining art of medicine. Once this review is complete, the findings will be disseminated through articles and publications nationally and globally, ensuring that the broader community can benefit from our insights regarding approaches and practices of BST and their impact on anticipated outcomes.